Opportunities for the use of the small-size accelerator VGIK-1 - Vinnikiov, D.V.; Buravilov, I.V.; Yuferov, V.B.; Ponomarev, A.N.; Tkachev, V.I. (Вопросы атомной науки и техники, 2019)
The experimental data on modification of the surface of metals, alloys and materials coated using the method of irradiation by a heavy-current electron beam with the energy of 300 keV have been given. The specimen surface structure was studied before and after the irradiation using the method of optic microscopy and the surface layer microhardness measurement. The method of electron microscopy was used to analyze the structure and the sizes of dispersed anode material. The films consisting of the crystals with the size of 6 to 8 nm were obtained. The mass transfer processes that occur in the material of metal targets made of Cu, Ti, Mo, Al were studied. The spatial map was compiled for the X-ray field of the plant. The experiments were carried out to define the action of X-ray radiation on the different types of conditionally pathogenic microflora, in particular such bacteria as Escherichia coli, Staphylococcus aureus, and Bacillus subtilis. The fields of application of the plant were defined. Представлено експериментальні результати по модифікації поверхні металів, сплавів і матеріалів з нанесеними покриттями методом опромінення потужнострумовим електронним пучком з енергією до 300 кеВ. Вивчена структура поверхні зразків до і після опромінення методом оптичної мікроскопії та вимірювання мікротвердості в поверхневому шарі. Методом електронної мікроскопії проведено аналіз структури і розмірів розпорошуваного матеріалу анода. Отримано плівки, що складаються з кристалів розміром 6…8 нм. Досліджено процеси масопереносу матеріалу металевих мішеней Cu, Ti, Mo, Al. Складено об'ємну карту рентгенівського поля установки. Проведено експерименти з впливу рентгенівського випромінювання на різні типи умовно патогенної мікрофлори: бактерії типу Escherichia coli, Staphylococcus aureus, Bacillus subtilis. Визначено подальші напрямки застосування установки. Представлены экспериментальные результаты по модифицированию поверхности металлов, сплавов и материалов с нанесенными покрытиями методом облучения сильноточным электронным пучком с энергией до 300 кэВ. Изучены структура поверхности образцов до и после облучения методом оптической микроскопии и измерения микротвердости в поверхностном слое. Методом электронной микроскопии проведен анализ структуры и размеров распыляемого материала анода. Получены пленки, состоящие из кристаллов с размером 6…8 нм. Исследованы процессы массопереноса материала металлических мишеней Cu, Ti, Mo, Al. Составлена объемная карта рентгеновского поля установки. Проведены эксперименты по воздействию рентгеновского излучения на различные типы условно патогенной микрофлоры: бактерии типа Escherichia coli, Staphylococcus aureus, Bacillus subtilis. Определены дальнейшие направления применения установки.